Life cycle assessment for circular biomanufacturing of lactic acid from sugarcane bagasse - Vanapalli, Kumar Raja; Parveen, Naseeba; Maity, Sunil K.; Parra-Saldívar, Roberto; Jacob, Samuel; Kumar, Gopalakrishnan; Kumar, Vinod (Elsevier, 2026)
Lactic acid (LA) is a top platform chemical with diverse applications in various industrial sectors. Sugarcane bagasse (SCB) is a significant waste stream during sugarcane processing. Our previous work was focused on the biomanufacturing of LA using fermentable sugars from SCB and techno-economic analysis. The current study evaluated the life cycle assessment (LCA) of SCB-based LA manufacturing for three different routes using the process models based on industrial-scale biorefinery – acid pretreatment & fermentation integrated with reactive distillation (ARD), alkali pretreatment & fermentation integrated with reactive distillation (AkRD), and alkali pretreatment & fermentation integrated with distillation (AkD). The environmental impacts were evaluated using attributional and consequential life cycle assessment (aLCA and cLCA). While aLCA was used to identify process hotspots by proportionally allocating environmental impacts, long-term impacts were assessed through cLCA by accounting for avoided products and additional burdens resulting from the upstream and downstream consequences of the processes. The aLCA analysis indicated that ARD had a 30–36 % superior environmental performance compared to AkRD and AkD, based on midpoint & endpoint impacts. The cooling water (45–47 %) and steam (27–29.1 %) during distillation, along with chemicals (18.4–24.2 %) in pretreatment and fermentation, were identified as environmental hotspots, with the respective values representing their proportionate contributions to the midpoint impacts across all scenarios. The cLCA depicted that LA recovered from the processes could offset environmental impacts by 34–44.2 %, emphasizing the long-term benefits of replacing the conventional LA manufacturing process. Moreover, valorisation of CO2, gypsum, and steam as by-products could significantly reduce environmental impacts. The process heat integration pinch technology further reduced steam and cooling water demands, cutting the impact by 26–27.5 %. These findings emphasize the importance of water recycling and energy integration for improving the overall sustainability of SCB to LA valorisation.
Keywords: Consequential LCA; Sugarcane bagasse; Lactic acid; Microbial fermentation; Reactive distillation; Sensitivity; 41 Environmental Sciences; 12 Responsible Consumption and Production; 4104 Environmental management; 4404 Development studies